2021
DOI: 10.1038/s41438-020-00447-1
|View full text |Cite
|
Sign up to set email alerts
|

Almond diversity and homozygosity define structure, kinship, inbreeding, and linkage disequilibrium in cultivated germplasm, and reveal genomic associations with nut and seed weight

Abstract: Almond [Prunus dulcis Miller (D.A. Webb)] is the main tree nut species worldwide. Here, genotyping-by-sequencing (GBS) was applied to 149 almond cultivars from the ex situ collections of the Italian Council for Agricultural Research (CREA) and the Spanish National Research Council (CSIC), leading to the detection of 93,119 single-nucleotide polymorphisms (SNPs). The study of population structure outlined four distinct genetic groups and highlighted diversification between the Mediterranean and Californian gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…SNPs called in this study, differently from those previously reported for the PSPP + P. fulvum germplasm collection [ 8 ], could be physically mapped onto the recently released pea genome [ 13 ], and therefore used for the genome-wide characterization of LD decay and selection signatures. In accordance with previous studies [ 31 , 32 ], markedly different rates of LD decay were observed among intraspecific populations ( Fig. 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…SNPs called in this study, differently from those previously reported for the PSPP + P. fulvum germplasm collection [ 8 ], could be physically mapped onto the recently released pea genome [ 13 ], and therefore used for the genome-wide characterization of LD decay and selection signatures. In accordance with previous studies [ 31 , 32 ], markedly different rates of LD decay were observed among intraspecific populations ( Fig. 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…A complete genetic identity was observed for the cultivars "Mollesca di Ruvo", "Troito", "Tuono" and "Stilla" (Table 2). The genetic similarity of "Tuono" with "Troito", as well as with other Italian and foreign cultivars such as "Supernova" [44], "Moncajo" and "Laurenne" [45], has been previously reported by other authors and is probably due to the extensive use of this cultivar in breeding programs, as they are good sources of self-compatibility [24,46,47]. Therefore, as "Mollesca di Ruvo" and "Stilla" also showed a high genetic similarity with "Tuono", we hypothesized that, together with "Troito", they could be Tuono-related cultivars, probably assigned different names due to their morphological diversity.…”
Section: Ssr Polymorphismsupporting
confidence: 52%
“…Several studies were conducted to characterize different almond germplasm and evaluate the level of genetic variability within populations, using different molecular markers, such as RAPDs [20,21], AFLPs [22] and SNPs [23,24]. In particular, microsatellites (SSRs), which are often the markers of choice thanks to their numerous advantageous features (hypervariability, codominance, multiallelic nature, high reproducibility and extensive genome coverage) [25,26], have been widely used for the evaluation of almond genetic diversity [27][28][29][30], germplasm management [31,32], genome mapping and syntheny analysis [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…they have very high h 2 ). Two of them—endocarp density and toxicity—are considered monogenic (Dicenta et al, 1993; Sánchez‐Pérez et al, 2007; Spiegel‐Roy & Kochba, 1981) while recent results by Pavan et al (2021) indicate that seed weight also has a very narrow genetic basis. However, given the wide genetic diversity across populations and the high genetic and phenotypic diversity of cultivated almonds (Fornés‐Comas et al, 2019; Halász et al, 2019; Socias i Company & Felipe, 1992), genetic variance for all traits (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Both seed size and kernel (endocarp) resistance have been described as highly heritable in almond (Dicenta et al, 1993; Spiegel‐Roy & Kochba, 1981). In fact, both traits might even be monogenic; endocarp resistance has been proposed to be controlled by the gene D‐Q (Sánchez‐Pérez et al, 2007) while recent genome‐wide studies have identified a single marker with a significant association with seed weight (Pavan et al, 2021). Given the high heritability of these three traits (seed toxicity, kernel resistance and seed weight) and the high diversity of cultivated populations (Socias i Company & Felipe, 1992), a sufficiently strong selection during feralization might cause a shift in phenotypic means, even over a relatively low number of generations.…”
Section: Introductionmentioning
confidence: 99%